Comparative study of effect of ionizing radiation on composites of wood flour in poliethylene and polypropilene matrixes using barium titanate as coupling agent - de Miranda, Leila Figueiredo; de Almeida, Jademir J. P.; Masson, Terezinha J; Munhoz Júnior, Antônio Hortêncio; Casimiro Pereira, Nilson; Gondim de Andrade e Silva, Leonardo (Revista Mackenzie de Engenharia e Computação, 2012)
This work deals with the effects of ionizing radiation on the properties of wood flour composites in polyethylene and polypropylene matrixes, using barium titanate as a coupling agent. The investigated compositions were carried out with polyethylene/ wood flour with barium titanate and polypropylene/wood flour with barium titanate using different wood flour concentrations of 10% and 20wt%. For the polyethylene it was also studied the addition of 30wt% of wood flour. Subsequently, the samples were molded by injection, irradiated and submitted to thermal and mechanical tests. The mechanical properties (hardness, impact strength and melt flow index (MFI)), as well as the thermal properties (thermal distortion temperature and Vicat softening temperature) of the composites, non irradiated and irradiated were determined. The samples were irradiated in irradiation doses of 10 kGy and 20 kGy in an electron accelerator. For the polyethylene the samples were irradiated at 30 kGy also. Regarding the mechanical properties of non-irradiated samples, the incorporation of wood four to polyethylene, resulted in a decrease of impact strength, tensile strength and melt flow index, while increasing the hardness and HDT, showing that the wood flour is ineffective as reinforcement agent, but acts like a biodegradable filler. There is no change in Vicat softening temperature. In case of the irradiated samples, there was observed a reduction in the impact strength, tensile strength, HDT, and thermal distortion temperature while increasing the hardness and tensile strength. The Vicat softening temperature was unchanged. Regarding the mechanical properties of nonirradiated samples, the incorporation of wood flour to polypropylene, promotes a decrease of impact strength, melt flow index and an increase in hardness and tensile strength, showing that the wood flour acts like a reinforcement agent. In the same way as to the irradiated samples, it was observed a decrease in the impact strength, hardness and thermal distortion temperature and an increase in the tensile strength and Vicat softening temperature. Keywords: Wood flour, barium titanate, ionizing radiation.